2015
DOI: 10.1002/jcop.21676
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Racialization Through Arts Practice: The Case of Participatory Theater

Abstract: This article describes two participatory theater projects undertaken by Western Edge Youth Arts in Melbourne and aimed at challenging racialization and fostering belonging among culturally diverse young people. Drawing from interview and archival data, we suggest that participatory theater provided the young people the opportunity to share and reflect on their lived experiences and re-present themselves, as well as gain resources for responding to the different issues associated with racialization. In the sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Telling stories based on experience is a powerful critical social location from which to speak (hooks, 1990). Theatre is an embodied artform, as such it provides space to play with affect (Gallagher et al, 2017) and fosters encounters with others through storytelling (Sonn, Quayle, Belanji, & Baker, 2015). In his research with temporary seasonal agricultural workers in Canada from Mexico and the Caribbean, Perry 2017demonstrates how theatre provides a unique space for exploring embodied practices and tacit or subconscious knowledge, particularly with marginalised people who are usually not deemed as 'knowers.'…”
Section: Theatre As Methodsmentioning
confidence: 99%
“…Telling stories based on experience is a powerful critical social location from which to speak (hooks, 1990). Theatre is an embodied artform, as such it provides space to play with affect (Gallagher et al, 2017) and fosters encounters with others through storytelling (Sonn, Quayle, Belanji, & Baker, 2015). In his research with temporary seasonal agricultural workers in Canada from Mexico and the Caribbean, Perry 2017demonstrates how theatre provides a unique space for exploring embodied practices and tacit or subconscious knowledge, particularly with marginalised people who are usually not deemed as 'knowers.'…”
Section: Theatre As Methodsmentioning
confidence: 99%
“…In addition to facilitating internal reflection and awareness, community-based theatre was a forum for minoritized young people to engage with perpetrators of injustices against them. Sonn, Quayle, Belanji, and Baker (2015) showed that the On the Radar Playback Theatre project was specifically designed to enable dialogue between minoritized youth and police. Youth discussed their marginalized status in the community, media misrepresentation, and experiences of racialization and criminalization by local police within structured workshops.…”
Section: Identification: Naming To Express and Understandmentioning
confidence: 99%
“…Engaging young people in interactions that require them to (re)consider identity, difference, and belonging was a characteristic of cosmopolitanism in theatre programs (e.g., Pruitt, 2015; Sonn et al, 2015; Vasudevan, 2014) For example, Sonn et al’s (2015) study of The Chronicles oral history theatre project explicated the use of storytelling and performance in fostering identity, community and belonging among Australian youth. The first stage of the project engaged youth in the exploration of the cultural histories and experiences of their families through interviews with parents, which the youth then retold through performances.…”
Section: Cosmopolitanism: Exploring Belonging and Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Participatory theater refers to approaches and strategies of involving the audience in the production and also inspiring them to act in their communities as a result of seeing a particular play. These projects include the Westville Prison Project in Durban, South Africa (Singhal 2004a); the Western Edge Youth Arts theater project to combat racism in Melbourne, Australia (Sonn et al 2015); the Radical Wallflowers and other grassroots disability theater groups in California (Lewis 2006); and Portland's Labor Players, one of the first labor theater troupes in U.S. history (Lembeke 1981).…”
Section: Previous Literature and Contextmentioning
confidence: 99%